Application of Moxibustion Method with Acupressure and Essential Oil Aromatherapy on Pain Reduction and Cervical Dilation During the First Stage of Labour - Fitria, Fitria; Ni Wayan Noviani; G.A Martha Winingsih (Babali Publisher, 2024)
Introduction: Discomfort, fear, and pain are major challenges for pregnant women during childbirth, potentially impeding the progress of labour. Many women opt for non-pharmacological methods, such as moxibustion, acupressure, and essential oil aromatherapy, to avoid medical induction due to their simplicity, accessibility, and cost-effectiveness. This study aims to evaluate the effectiveness of these combined methods in reducing pain and accelerating cervical dilation during childbirth. Method: This study employed a quantitative research design with a two-group pre-post test approach. The sample comprised 30 parturient women in the first stage of labour at the Independent Midwifery Practice within the Denpasar Health Centre’s service area, divided into intervention and control groups. Data analysis was conducted to evaluate differences in pain management between the two groups using the Wilcoxon test, while the effectiveness of cervical dilation treatment in both groups was assessed using the Mann-Whitney test. Results: The findings indicated a significant difference in pain levels (0.000 < 0.05) following the application of the moxibustion method with acupressure and essential oil aromatherapy. However, there was no significant difference in cervical dilation between the control and intervention groups post-treatment (0.902 > 0.05). Conclusion: The moxibustion method, combined with acupressure and essential oil aromatherapy, did not show a significant difference in cervical dilation between the control and intervention groups. This study has several limitations, including a relatively small sample size and a short observation period.